KETERAMPILAN BERPIKIR KRITIS DALAM PEMBELAJARAN AL-QURAN DAN HADIS: CRITICAL THINKING SKILLS IN THE STUDY OF THE QURAN AND HADITH - ismail, usep; Firmansyah, Muhamad; Edy (Edusifa: Jurnal Pendidikan Islam, 2023)
Critical Thinking Skills in learning the Qur'an and hadith create an integral foundation for a true understanding of Islam. The stages of developing these skills involve deep understanding, contextual analysis, critical interpretation, and relevance to contemporary reality. Motivation for critical thinking, such as an invitation to reflect, emphasis on knowledge, and the pursuit of truth, is explicitly mentioned in the Qur'an and hadith. The integration of critical thinking skills in Islamic education not only adds a spiritual dimension, protects against misinterpretation but also produces an intellectual and reflective community capable of responding to the challenges of the times.